Epidemiology, mechanisms, and clinical impact of bacterial heteroresistance - Linna Xu; Xiaofen Mo; Hui Zhang; Fen Wan; Qixia Luo; Yonghong Xiao (npj Antimicrobials and Resistance)
Abstract Bacterial heteroresistance, a phenomenon where subpopulations within a bacterial strain exhibit significantly reduced antibiotic susceptibility compared to the main population, poses a major challenge in managing infectious diseases. It is considered an intermediate stage in the evolution of bacteria towards full resistance. Heteroresistant strains often have a minimal inhibitory concentration (MIC) that appears sensitive, making detection and differentiation in clinical settings difficult. As a result, the impact on clinical outcomes is challenging to fully understand, as it often remains “hidden”. In recent years, heteroresistance has received increasing attention. However, it is still poorly understood and underappreciated. We provide an overview of the epidemiology, mechanisms, and clinical impact of heteroresistance. This review underscores the critical importance of understanding and addressing bacterial heteroresistance in the ongoing fight against antibiotic resistance and infectious diseases.